Management of Psychosis and Schizophrenia by Primary Care GPs: A Cross-Sectional Study in Spain - Jesús Sepúlveda-Muñoz; Casta Quemada González; María M. Hurtado Lara; Ángel Manuel Gutiérrez García; Celia Martí-García; José María García-Herrera Pérez-Bryan; José Miguel Morales-Asencio (Journal of Primary Care & Community Health)
Aim: To investigate the detection and initial management of first psychotic episodes, as well as established schizophrenia, within the primary care of the Andalusian Health System. Background: Delay in detecting and treating psychosis is associated with slower recovery, higher relapse risk, and poorer long-term outcomes. Often, psychotic episodes go unnoticed for years before a diagnosis is established. Primary care physicians are crucial for early recognition of psychosis and schizophrenia, especially in Spain, where primary care is the main entry point to healthcare services. Methods: Cross-sectional exploratory study. All active primary care physicians in the Malaga Guadalhorce Health District were invited to participate. Due to the COVID-19 pandemic, the survey was conducted online. The survey, adapted and validated for the local context, included 22 items and 5 sociodemographic questions covering early detection, treatment options, physical health monitoring, and management challenges. Descriptive and bivariate analyses summarized the data and explored correlations between key variables. Findings: The study included 142 primary care physicians (response rate 35.5%), with 28.9% men and 71.1% women, primarily from urban areas (83.1%). Most had completed residency training (86.6%), with 79.6% receiving psychiatric training. However, only 5.6% had participated in training sessions in the last 5 years, with all such sessions lasting less than 30 h. Physicians typically managed 0-10 patients with diagnosed schizophrenia and saw these patients 2 to 3 times annually. They often felt capable of managing these patients, especially with mental health consultancy support. Physical health monitoring was common, though some relied on mental health services to do this. Collaboration with mental health services was moderate, with high utility perceived for having a list of patients with severe mental disorders in their care panel. Conclusions: Family physicians are generally confident in managing psychosis and schizophrenia but lack recent specialized training. Mental health consultancy services are valued, but collaboration with these services needs improvement. Clear guidelines and enhanced training are essential to ensure comprehensive care, addressing both mental and physical health needs of these patients.